O acesso à justiça no Estado democrático de direito: a reforma trabalhista na contramão do direito fundamental à assistência jurídica integral e gratuita - Sousa, Leonardo Barbosa de (2019)
The present work aims to deepen the studies on the fundamental rights of access to justice and full legal assistance in the context of the Labor Reform. We divide the work into three chapters: the first on the fundamental right of access to justice; the second on the role of procedural labor law as an element of effective social and fundamental rights of workers; and the third and final chapter on labor reform and its influence on these rights. The method used was the dialectic, considering the confrontation of the legal instruments that subsidize the fundamental rights of access to justice and of the integral and gratuitous legal assistance with the text of the labor reform. The theoretical basis was Mauro Cappelletti's procedural philosophy on access to justice and the process as instruments for the realization of material rights. At the same time, we turn to the modern processualists of civil and labor law, giving the work a dogmatic aspect. There was no field survey. The objective was to demonstrate the legal nature of human and fundamental right of the principle of non-exhaustiveness of jurisdiction and full and free legal assistance, as well as the social and fundamental rights of workers, in order to counter normative reform treatment contributed positively or negatively to the promotion of social justice and the fundamental right of access to justice. We conclude at the end that the changes promoted by the labor reform regarding the right to full and free legal assistance bring economic oppression to the worker, distorting the social purpose of the process and, thus, creating obstacles to access to justice, especially access to order legal basis. Key-